Kajian Populasi dan Serangan Hama Penggerek Jagung Ostrinia furnacalis (Lepidoptera: Phyralidae) dan Helicoverpa armigera (Lepidoptera: Noctuidae) - Patty, John Alfred; Uruilal, Costanza (Fakultas Pertanian, Universitas Pattimura, 2025)
Maize (Zea mays) plays an important role in the diet of the community after rice and has the potential to be a substitute for rice. One of the causes of the decline in corn productivity is the presence of plant-disrupting organisms, namely corn stalk borer (Ostrinia furnacalis) and corn cob borer (Helicoverpa armigera). Waimital Village, Kairatu Subdistrict, West Seram Regency is one of the corn center villages where farmers rely on synthetic insecticides in pest control without knowing the intensity of the damage caused. This study aims to determine the number of populations and the intensity of damage caused by Ostrinia furnacalis and Helicoverpa armigera pests that attack corn plants, as well as the relationship between the number of populations and the intensity of damage to each pest. The method used was the survey method in the corn planting area of Waimital village, then 5 farmers were taken with the determination of plants divided into 4 plots with details of each plot of 10 plants. The results of this study showed that the average population of Ostrinia furnacalis was 4.37 heads, the average population of Helicoverpa armigera was 1 head, the average damage intensity of Ostrinia furnacalis was 42.71% (medium criteria), the average damage intensity of Helicoverpa armigera was 11.83% (light criteria) and the relationship between Ostrinia furnacalis and Helicoverpa armigera pest populations and damage intensity showed that the larger the pest population, the higher the damage intensity.